1987
DOI: 10.1182/blood.v69.4.1128.1128
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12-responsive neonatal megaloblastic anemia and homocystinuria with associated reduced methionine synthase activity

Abstract: We present findings on an infant with neonatal megaloblastic anemia, homocystinuria, and neurologic dysfunction that included developmental delay and tonic seizures. There was no methylmalonic aciduria. Cyanocobalamin therapy was accompanied by complete hematologic and neurologic recovery, diminished homocystine excretion, and subsequently normal neurologic development. Cultured fibroblasts and lymphoblasts showed a reduced methionine synthase activity and a growth requirement for methionine. Cobalamin incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This suggested that the infant had a unique block in MS or the synthesis of MeCbl. Subsequently, two other patients were described with the same symptoms (Refs 99 , 100 ). Broken cell extracts from the original patient revealed that with added reducing agents, MS worked perfectly.…”
Section: Complementation Groups Affecting Only Methionine Synthasementioning
confidence: 99%
“…This suggested that the infant had a unique block in MS or the synthesis of MeCbl. Subsequently, two other patients were described with the same symptoms (Refs 99 , 100 ). Broken cell extracts from the original patient revealed that with added reducing agents, MS worked perfectly.…”
Section: Complementation Groups Affecting Only Methionine Synthasementioning
confidence: 99%
“…Cobalamin treatment is usually given for anemia and biochemical abnormalities in patients, and cyanocobalamin is used for neurological and hematological improvement but hydroxycobalamin has been more effective than cyanocobalamin. [ 4 5 ] Hydroxycobalamin is beneficial for neurologic development. [ 4 ] However, the impact of treatment is less in biochemical parameters and generally hyperhomocysteinemia persists.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Cobalamin treatment is usually given for anemia and biochemical abnormalities in patient, and cyanocobalamin is used for neurological and hematological improvement, but hydroxycobalamin has been more effective than cyanocobalamin. [ 4 5 ] Betaine is a potent methyl group donor, which has a role in remethylation of homocysteine to methionine using betaine–homocysteine methyltransferase that bypass methylcobalamin-dependent pathway. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Because methyl-B 12 is a cosubstrate in the methionine synthase reaction, these mutations appear as functional methionine synthase deficiencies. 89,[114][115][116][117][118] No discrete mutations of methionine synthase associated with hyperhomocysteinemia have been described.…”
Section: Methionine Synthasementioning
confidence: 99%